2009
DOI: 10.1021/es8022804
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically Induced Changes in Dissolved Organic Matter Identified by Ultrahigh Resolution Fourier Transform Ion Cyclotron Resonance Mass Spectrometry

Abstract: Sunlight-induced molecular changes have been observed in two samples of dissolved organic matter (DOM) collected in the Cape Fear River system, North Carolina, USA. The molecular composition of a water sample collected in the Black River (sample B210, salinity 0) and another water sample collected within the Cape Fear River estuary (sample M61, salinity 13.7) were analyzed using an ultrahigh resolution 9.4 Tesla (T) electrospray ionization Fourier transform ion cyclotron resonance mass spectrometer. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
192
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(221 citation statements)
references
References 40 publications
25
192
3
1
Order By: Relevance
“…Probably this mechanism can be disregarded for this work. Similar K C results were found by Merdy et al 51 Solar radiation effect on the complexation capacity of AHS Some studies have already shown that solar radiation is able to degrade natural organic matter 19,48 and to interfere in the interaction of these metal species. However, few studies with the same AHS thematic have been addressed in the literature.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Probably this mechanism can be disregarded for this work. Similar K C results were found by Merdy et al 51 Solar radiation effect on the complexation capacity of AHS Some studies have already shown that solar radiation is able to degrade natural organic matter 19,48 and to interfere in the interaction of these metal species. However, few studies with the same AHS thematic have been addressed in the literature.…”
supporting
confidence: 80%
“…A decrease of fluorescence intensity due to exposure to natural or artificial radiation was observed by other authors by dissolved organic matter. 19,49,52 Gonsior et al 19 verified a fluorescence intensity reduction of 24% for the Preto River water, in California, and verified a greater degradation in compounds that contain fluorescent chromophore groups. They also observed that a concentration of DOC remained constant during radiation.…”
Section: Fluorescence Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…under the assumption that most DOM oxygen is bound to carbon by a double bond (40,41). In contrast with DBE, the DBE−O distribution is lower in bog than in fen DOM (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The burgeoning use of mass spectrometry in DOM studies has tremendously advanced our molecular-level understanding of DOM dynamics [11][12][13][14][15] . Recent developments in data processing now enable us to analyze the detailed molecular composition of DOM as a function of environmental gradients over a large number of samples.…”
mentioning
confidence: 99%